Awareness and Usage of E books Among Students of Panjab University, Chandigarh - Sood, Seema; Singh, Neeraj Kumar; Sumi, Suman; Tewari, Deepika (DESIDOC Journal of Library & Information Technology, 2024)
The advancement of digital technologies has an impact on how information is disseminated and made accessible in the academic world. The use of digital resources has grown significantly, with e-books becoming a valuablemeducational resource. Panjab University library is spending a huge amount of money in terms of subscribing to a number of e resources to fulfill the information demand of faculty and students. PU library started subscribing to e-books from the year 2008 and presently a diverse collection of e-books from reputed publishers are available for the users. Since no such study has been conducted to examine the use and awareness of e-books, to determine level of relevance of e-books, subscribed by Panjab University, it is therefore imperative to investigate how Panjab University students use and are aware of their subscription to e-books. A total of 400 questionnaires were distributed using a simple random sampling method and 202 responses were received. This paper also explores the usage, relevance and the difficulties encountered while accessing e-books. For this purpose, an online survey was conducted amongst post graduate students and research scholars of Panjab University. Majority of the respondents73 (66.4 %) are accessing e-books through University Library website. 72 (62.6 %) of respondents express thatfriends and teachers helped them to know about availability of e-books in the library. Respondents encountere problems i.e. difficulties to login the sites, low speed of internet and restrictions in downloading etc. while accessing e-books. This study offers some useful and practical suggestions that can help libraries to enrich their e-book collections. The findings of the study will be helpful in developing e-book collection while keeping user needs in mind to enhance overall digital learning experience.